Variability in Host Specificity and Functional Potential of Antarctic Sponge-Associated Bacterial Communities - Cristi, Antonia; Parada-Pozo, Génesis; Morales-Vicencio, Felipe; Cárdenas, César A.; Trefault, Nicole (Frontiers in Microbiology, 2022)
Sponge-associated microorganisms are essential for sponge survival. They play an important role in recycling nutrients and, therefore, in the maintenance of the ecosystem. These microorganisms are diverse, species-specific, and different from those in the surrounding seawater. Bacterial sponge symbionts have been extensively studied in the tropics; however, little is known about these microorganisms in sponges from high-latitude environments. Sponges can cover up to 80% of the benthos in Antarctica and are crucial architects for the marine food web. In this study, we present analyses of the bacterial symbionts of three sponges: Haliclona (Rhizoniera) sp., Hymeniacidon torquata and Isodictya kerguelenensis from the Western Antarctic Peninsula (WAP) with the aim to determine variations on the specificity of the bacteria-sponge interactions and potential signatures on their predicted functional profiles. We use high throughput 16S rRNA gene sequencing of 30 sponge individuals inhabiting South Bay (Palmer Archipelago, WAP) to describe their microbiome taxonomy and diversity and predict potential functional profiles based on this marker gene. Our work shows similar bacterial community composition profiles among the same sponge species, although the symbiotic relationship is not equally conserved among the three Antarctic sponges. The number of species-specific core Operational Taxonomic Units (OTUs) of these Antarctic sponges was low, with important differences between the total abundance accounted for these OTUs. Only eight OTUs were shared between the three sponge species. Analyses of the functional potential revealed that despite the high host-symbiont specificity, the inferred functions are conserved among these microbiomes, although with differences in the abundance of specific functions. Hymeniacidon torquata showed the highest level of intra-specificity and a higher potential of pathways related to energy metabolism, metabolisms of terpenoids and polyketides, and biosynthesis of other secondary metabolites. Overall, this work shows variations in the specificity of the sponge-associated bacterial communities, differences in how hosts and symbionts establish their relations, and in their potential functional capabilities.